Melatonin inhibits high voltage activated calcium currents in cultured rat dorsal root ganglion neurones - Ayar, A; Martin, DJ; Ozcan, M; Kelestimur, H (Elsevier Ireland Ltd, 2001)
The actions of melatonin on high-voltage activated calcium channels (HVACC) and intracellular free Ca2+ concentration in cultured dorsal root ganglion (DRG) neurones from neonatal rats were investigated using the whole-cell patch clamp and the fura-2 fluorescence ratio Ca2+-imaging techniques. HVACC were pharmacologically and biophysically isolated and the effects of melatonin were investigated. Extracellular application of melatonin inhibited HVACC in a dose dependent manner. In calcium imaging experiments, application of extracellular recording medium containing 30 mM KCI evoked increases in intracellular free Ca2+ that were dependent upon external Ca2+ ions. This increase was prevented by both low (10 muM) and high dose (100 muM) of melatonin pre-treatment. The results of this study indicate that the pineal hormone melatonin has inhibitory actions on voltage dependent calcium entry in cultured rat DRG neurones. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: melatonin; fura-2; sensory neurone; patch clamp; rat